Motivation of Job Seekers to be Civil Servants - Irsutami Irsutami; Andre Agus Setiawan Sitepu (Journal of Applied Accounting and Taxation, 2018)
The large number of companies established in Batam city resulted to the opening of the many jobs. But the large number of private companies erected in Batam is not making job seekers to lose their interest to register themselves into the civil service. In 2014 there are 3.873 people who apply to be civil servants for 94 formations. The purpose of this research is to investigate the main motivation of job-seeker on Batam to become civil officer, based on gender restriction and family factor. Sample used in this research are 268 university students that have been studied public sector accounting on Batam. To determine the results, writer used qualitative research method with questionnaire. Gathered data are analyzed with confirmatory factor analysis. Stabilized future and secure environment are the main factor for the job-seeker on Batam to become civil officer, based on gender restriction and family factor. This study intended specifically to the staffing Agency of Batam to be material consideration in hiring. This research is limited to students who have studied public sector accounting in batam, then the author suggested to expand the sample in the future research.